The Development of the Fundamentals of a Silicon-Based Point-Of-Care Device for Future Electrochemical Detection of Pathogen Mycobacterium Avium Subspecies Paratuberculosis (MAP) DNA. - Jankkila, Patricia (My University, 2019)
This 60 ECTS M.Sc. thesis project aimed to develop the fundamentals for a straightforward, low-cost silion-based three-electrode sensing essay for future on-site detection of Mycobacterium avium subspecies paratuberculosis (MAP). The backbone of the sensor development was in-hood metal-assisted chemical etching of silicon using hydroﬂuoric acid and three diﬀerent metals, namely gold, silver and platinum. The modiﬁed silicon pieces were analyzed using SEM and furthermore assembled on glass slides along two commercial inks to create the three-electrode setup, and the silicon electrodes were evaluated using cyclic voltammetry and chronoamperometry using ferricyanide and methylene blue redox solutions at pH 7 and room temperature. Gold-coated silicon was evaluated the furthest and the results suggest an overall reversible system though the sensor prototype stability was lacking due to its crude nature and assembly. The electrochemical testing showed variance in the system’s ability to detect diﬀerent concentrations of redox solutions, but high degrees of reversibility and promising promising potential scanning windows. In order to analyze the silicon electrodes further, more reliable sensor components and increased metal-to-silicon adhesion would be necessary.
Keywords: Analytisk kemi; Annan kemi; Annan kemiteknik; Livsvetenskaper; Analytical Chemistry; Other Chemistry Topics; Other Chemical Engineering; Life Science